CONTRIBUTIONS OF PHYSICAL EDUCATION ON PSYCHOSOCIAL DEVELOPMENT IN PRESCHOOL (Fiep Bulletin - online, 2014)
The school is considered as educational environment, which aims to provide the student not only expertise in various disciplines, but also provide sports practices essential to the general development of the child. Physical education class is that the child will have greater social interaction, know what to relate in group as well as learn to respect, in addition to the rules and regulations, the differences between people. This article aims to analyse the physical education as an important factor in psychosocial development in preschool, because physical education promotes diversity of experiences and situations through experience, where possible the child finding its threshold, the valuation of your own body, the understanding of their abilities. It is from these findings that the child begins to use more easily to body language, assisting the progress regarding the discovery of physical, cognitive and psychosocial capacity.
Keywords: Pre-School; physical education; psychosocial Development